2022
DOI: 10.3390/genes13020338
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses of the Fungus Paraconiothyrium sp. Isolated from the Chinese White Wax Scale Insect Reveals Its Symbiotic Character

Abstract: The Chinese white wax scale, Ericerus pela, is an insect native to China. It harbors a variety of microbes. The Paraconiothyrium fungus was isolated from E. pela and genome sequenced in this study. A fungal cytotoxicity assay was performed on the Aedes albopictus cell line C6/36. The assembled Paraconiothyrium sp. genome was 39.55 Mb and consisted of 14,174 genes. The coding sequences accounted for 50.75% of the entire genome. Functional pathway analyses showed that Paraconiothyrium sp. possesses complete path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…E. pela had an extremely biased A + T content of 88.21%, higher than all the other nine Coccoidea species, which indicated an adaptation to a significantly high requirement for nitrogen. This was in accordance with the existence of symbiotic fungi, which could also serve as a nitrogen provider in vivo E. pela [ 18 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…E. pela had an extremely biased A + T content of 88.21%, higher than all the other nine Coccoidea species, which indicated an adaptation to a significantly high requirement for nitrogen. This was in accordance with the existence of symbiotic fungi, which could also serve as a nitrogen provider in vivo E. pela [ 18 ].…”
Section: Discussionsupporting
confidence: 83%
“…Most Coccoidea species are agriculture and forestry pests, except for very few species with a high economic value, such as the Chinese white wax scale insect Ericerus pela (Chavannes, 1848) [ 17 ]. Previous work has related to E. pela ’s use in biological research, molecular research, and the popularization of relevant applications [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Regarding its breeding history, people initially started to collect white wax as early as approximately the 3rd century AD in China [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As well as virulence factors, secondary metabolites play an important role in fungal pathogenicity in humans [ 16 ]. Paraconiothyrium brasiliense produces various secondary metabolites, including terpenes, polyketides, and aromatic compounds that have a wide range of biological activities [ 17 ]. In this study, we identified 27 genes encoding DFVF-HUM involved in secondary metabolite synthesis and four genes related to terpenoid metabolism, which were associated with human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we successfully isolated the fungi Paraconiothyrium sp. YMF1.07793 from the Chinese white wax scale insect (Ericerus pela) and revealed the existence of a symbiotic relationship between the fungus symbiont and the host based on amino acid and vitamin metabolic complementation [9].…”
Section: Introductionmentioning
confidence: 99%